Runtuhnya Ketatanegaraan dan Krisis Demokrasi: Korupsi dan Pudarnya Keadilan - Ardiyansyah, Amzar; Al Muttaqien; T Yasman Saputra; Umar Mahdi (Locus Journal of Academic Literature Review, 2025)
This study analyzes the collapse of constitutional governance and the democratic crisis in Indonesia by focusing on the weak implementation of the Constitution, the persistence of corruption, and the erosion of justice in law enforcement. The research employs a normative juridical method using statutory and case approaches, supported by academic literature and national news reports. The findings reveal that the principles of popular sovereignty and the rule of law, as mandated by the 1945 Constitution of the Republic of Indonesia, are often implemented merely in a formalistic manner, while political power remains concentrated among elites. Corruption has emerged as a key determinant undermining democratic legitimacy and triggering a crisis of public trust, as demonstrated by the nationwide protests in August–September 2025. The decline of justice is further reflected in discriminatory law enforcement“sharp downward, blunt upward” and the lack of independence among law enforcement institutions. This study recommends constitutional reform through further amendments, strengthened checks and balances, institutional restructuring, and the consolidation of substantive democracy to realize social justice and popular sovereignty as envisioned by the Constitution.